Fawaid al-Ansyithah ghair al-Shafiyyah li Tadris al-Lughah al-‘Arabiyyah fi al-Madaris al-‘Arabiyyah - Ahmed, Mohamed Mohi El-Din; Gad, Fardous Ahmed (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
Arabic schools seek to improve the teaching of the Arabic language, through the use of activities that motivate the student to learn and use the Arabic language. Student who want to learn to speak Arabic require a lot of practice through activities that require speaking. This study aims to highlight the experience of Arabic schools in Brunei in using non-class activities. This study describes and analyses the benefits of non-class activities for teaching Arabic at the Arabic schools in Brunei. Arabic schools have taken steps to develop the teaching of the Arabic language, and have increased the activities that push students to practice and use the Arabic language. They have managed and prepared Arabic plays and competitions at the classroom level, and the winning teams represents each school and compete against other Arabic schools in Brunei. Additionally, each school conducts public speaking competitions, group speeches, singing competitions, Arabic calligraphy, and other activities. Arabic schools also organize many events to introduce Arabic culture. Arabic schools push students to use the Arabic language at all events and occasions. Arabic schools organize Arabic language festivals and exhibitions, Arabic language week and open day. This study recommends the necessity of paying attention to classroom and non-classroom activities in teaching Arabic, and urges students to use the Arabic language in research, listening, reading, writing, and speaking the Arabic language inside and outside the classroom.